Patient’s confidentiality policy breach among nursing students - Patricia Sator; Hillwan Dionoly Justine; Christine Beverly Tiandun; Michelle Julius; Rodhiah Khalilah Ismail Khalil (2020)
Nursing is a regulated profession. Hence, the global commitment for nurses to maintain standards of practice is vital to deliver safe and competent care. Written policies will eliminate uncertainty, ambiguity, and legal issues. For this study, it focused on the importance of the nursing students to understand and practice the regulation on patient’s confidentiality in healthcare setting with the usage of technology such as social media. There is a case like nursing student infringe the privacy of patients with the information they posted on social media, such as posting a patient’s photos or videos without valid consent. Methods: This study is a quantitative, cross-sectional survey design. The respondents were selected as convenience sampling of 120 nursing students from the Faculty of Medicine and Health Sciences, Universiti Malaysia Sabah (FMHS, UMS). Results: There are 7.4% nursing students intentionally posted in social media, 18.0% maybe and 73.8% unintentionally. And for their guilty feeling after committing confidentially policy breach on patient, there are 8.2% said NO, 32.8% said MAYBE and 59% said YES. Overall, the nursing students are aware of the patient’s confidentiality but there is still a leakage in practicing full nursing standards and regulation. Further study recommended to explore more on this issue. Conclusion: As a conclusion, this study is relevant to conduct among the nursing students to gain their understanding regarding the responsibilities as a future nurse in maintaining the patient’s confidentiality as one of the most important nursing practices to ensure quality of care and continuation of professional service of nursing profession.